Diagnostic delay in progressive multifocal leukoencephalopathy - Miskin, Dhanashri P. (Ann Clin Transl Neurol, 2016)
We investigated delay in diagnosing progressive multifocal leukoencephalopathy (PML). The median time from initial symptom to diagnosis was 74 days (range 1–1643) in 111 PML patients seen at our institution from 1993 to 2015. Another diagnosis was considered before PML in nearly two–thirds, and more than three–quarters of patients suffered from diagnostic delay greater than 1 month, irrespective of their underlying immunosuppressive condition. Extended diagnostic delay occurred more frequently in patients with possible PML, and among HIV (+) patients with higher CD4(+) T‐cell counts at symptom onset. Prompt diagnosis may improve survival of PML in so far as immune reconstitution can be effected, and prevent unnecessary interventions.